Slow flow or prolonged arterial phase in coronary arteries is the cause of ischemia or sudden death in patients with dilated cardiomyopathy. (14th October 2021) - Le, M; Nguyen, T; Bui, H.O.A; Duong, H.A.I; Do, Q
Abstract: Background: In patients with dilated cardiomyopathy (DCM), the patients could be symptomatic or presented with recurrent fluid overload, syncope or sudden cardiac death (SCD) while the coronary arteries were patent. The aim of our study was to use the coronary flow abnormalities to stratify the high risk symptomatic versus the low risk asymptomatic patient with DCM. Methods: Consecutive patients with DCM were enrolled. Twenty patients with normal ejection fraction (EF) without coronary artery disease served as control. The study patients were checked for symptoms (fluid overload, syncope, SCD) and re-admission. All patients underwent a new coronary angiographic technique with injection of contrast until all the coronary arteries were completely filled. As the injection of contrast stopped, the blood in white color moved in and the blood movement could be clearly observed. The angiogram was recorded from the entry of blood flow until all the contrast was cleared. During the review, the investigators downloaded, selected the angiogram from the electronic medical record, tapped on the Key Image and used the Up and Down arrow to move the images, frame-by-frame. Each frame represented a 0.06-second recording. The duration of the arterial phase was calculated starting the time when the blood entered the ostium of the index artery until all the contrast disappeared from the distal vasculature. At the same time, an AI program was trained to measure the length of the arterial phase by Machine learning, supervised and unsupervised Deep Learning and Convoluted Neural Networks. (Figure 1) The AI programs compared the time when the arteries were full with contrast until there was no contrast left in the distal vasculature. (Figure 2) Results: One hundred patients with DCM were consecutively enrolled. Twenty patients served as control. In the control group with normal flow and EF, the duration of the arterial phase was 24–30 frames (1.44 to 2 seconds). In the study group, seventy patients had extremely prolonged arterial phase (average of 120 frames or >8 seconds (p<0.05). These patients were very symptomatic and had recurrent hospitalizations. Thirty patients had normal arterial phase of <2 seconds. These patients had shorter length of stay (<3 days), became asymptomatic after only 2 days of treatment and had rare readmission. (p<0.05) The AI programs confirmed the results of the arterial phases calculated manually by junior investigators. Conclusions: In patients with DCM, the extreme prolonged arterial phase caused ischemia in the myocardium even there was no coronary artery disease. This ischemic burden triggered recurrent ventricular dysfunction, arrhythmia, syncope and SCD. The patients with normal arterial phase became asymptomatic after optimal medical treatment. With these results, more effective prevention and management could be achieved for high risk symptomatic patients with high mortality and readmissions. Funding Acknowledgement: Type of funding sources: None.